Engineering of the Substrate Pocket of α-ketoglutaric Semialdehyde Dehydrogenase for Improving the Activity toward 3-hydroxypropanal - Park, Ye Seop; Nasir, Abdul; Nguyen-Vo, Thuan Phu; Ryu, Huichang; Seok, Joo Yeon; Jung, Gyoo Yeol; Park, Sunghoon; Yoo, Tae Hyeon (Biotechnology and Bioprocess Engineering, 2023)
3-Hydroxypropionic acid (3-HP) is a key building block for value-added chemicals. A biological route for synthesizing this molecule is two-step enzymatic reactions; dehydration of glycerol to 3-hydroxypropanal (3-HPA) by glycerol dehydratase and then oxidation of 3-HPA to 3-HP by aldehyde dehydrogenase. Here, we report an aldehyde dehydrogenase, an engineered α-ketoglutaric semialdehyde dehydrogenase (KGSADH) from Azospirillum brasilense. The variant, named 2C10, was obtained by applying a large KGSADH library to a selection method based on a 3-HP-responsive transcription factor and then a screening method for observing the activities of individual clones. 2C10 exhibited a 4.65-fold higher catalytic activity (kcat/Km: 100 ± 7.1 s−1mM−1) toward 3-HPA than the wild-type enzyme. The flask culture of Pseudomonas denitrificans with 2C10 resulted in an approximately 30% increase in 3-HP titer (43.2 mM) compared with that obtained using wild-type KGSADH (33.1 mM). Molecular dynamics simulations suggested that compared to the wild-type enzyme, 2C10 has a less flexible and smaller binding pocket for aldehyde substrates.
Keywords: 3-hydroxypropanal; 3-Hydroxypropionic acid; Aldehyde dehydrogenase; Building blockes; Dynamics simulation; Enzyme engineering; Molecular dynamic simulation; Semialdehyde dehydrogenase; Value-added chemicals; Wild-type enzymes; 3-Hydroxypropanal; 3-Hydroxypropionic acid; aldehyde dehydrogenase; enzyme engineering; molecular dynamics simulation